Construction and Validation of Teachers Family Environment Scale (TFES) - Balamurugan, Anselm (Journal of Research in Vocational Education, 2026)
The purpose of this study was to assess the influence of family environment of secondary school teachers’ absenteeism in Chennai, Kanchipuram and Thiruvallur Districts. The sample of 100 secondary teachers was collected from 20 schools that located in Chennai, Kanchipuram and Thiruvallur districts respectively. The simple random sampling technique was adopted to collect the data from the teachers, who were working in the secondary school level. The data was collected by distributing questionnaire using a 5 - point Likert scale to study 53 items of teachers family environment scale for the polite study. Consequently, the responses were subjected to critical ratio analysis of ‘t’ test and based on the ‘t’ ratio that is greater than (1.96) at 0.01 level for each item, have been selected and rest of the items were deleted. In order to, set the final draft of the teachers family environment scale, out of 53 items 38 items were selected eventually. Hence, the investigators believed that the 38 items in the scale were meaningful and reflect the family environment of the secondary school teachers and it would be helpful to measure how the family environment of secondary school teachers influences on their absenteeism to the school.